Back Cover: Superoxide Disproportionation Driven by Zinc Complexes with Various Steric and Electrostatic Properties (Angew. Chem. Int. Ed. 47/2013). Issue 47 (4th November 2013) - Wada, Akira; Jitsukawa, Koichiro; Masuda, Hideki
<x xml:space="preserve">Abstract</x> To illuminate an unexplained role of the zinc site of copper–zinc superoxide dismutase (Cu‐Zn SOD), synthetic zinc complexes as models of Cu‐Zn SOD were spectroscopically and structurally characterized. In their Communication on page 12293 ff., H. Masuda et al. describe the induction of the superoxide disproportionation reaction in the electrostatic sphere of the zinc complexes and elucidate that the reaction efficiency depended on both the Lewis acidity and the coordination structure of the zinc center.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>